Practice-oriented training of vocational teachers in renewable energy for post-war reconstruction of Ukraine - Radkevych, V.; Radkevych, O.; Pryhodii, M. (Problems of Engineer-Pedagogical Education, 2023)
The teachers training for renewable energy requires a special approach, as this industry is dynamic, multifaceted, and in demand for the post-war reconstruction of Ukraine. Training energy specialists, particularly in the context of green energy, is an important task that involves taking into account a number of challenges and opportunities. In addition, they must have practical skills and experience, as this is an important component of training in the renewable energy sector. The European Commission plays a special role in shaping renewable energy policy, setting important standards and requirements in this area. It has been proven that the development of renewable energy has several key trends. These include innovations in technology, investment growth, changing consumer attitudes, and political movement towards "green" technologies. It has been established that practice-oriented training has a number of characteristic features that distinguish it from more traditional, theoretically oriented approaches to education: emphasis on the practical application of knowledge; integration of theory and practice; close connection with industry. The teachers training for renewable energy necessitates the introduction of new mechanisms for designing content and teaching methods. Teachers of vocational education institutions should have in-depth knowledge of renewable energy, including modern technologies, development strategies, energy saving and greening of production, and be able to transfer this knowledge to students. It is substantiated that the training of teachers for vocational education in the field of energy may include the use of various methods aimed at developing the necessary competencies: project-based learning; interactive learning; internships and partnerships with industry; continuous professional development; case method; mentoring; collaborative learning; distance learning; internships, etc.